1975
DOI: 10.1002/ijc.2910160207
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between nasopharyngeal carcinoma and the HL‐A system among tunisians

Abstract: Previous reports have demonstrated an association between the HL-A system and risk for nasopharyngeal carcinoma among the Chinese in Singapore. The present paper describes an investigation of HL-A profiles among NPC cases and non-NPC controls from Tunisia, to determine whether a similar association occurs in a different ethnic group. A total of 109 NPC cases and 84 controls were typed. At the second HL-A locus the results were similar to those found in Singapore, but the effect was less marked and did not reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
22
0
3

Year Published

1980
1980
2005
2005

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(27 citation statements)
references
References 7 publications
2
22
0
3
Order By: Relevance
“…On the basis of historical, linguistic and classical genetic data, the Sardinians appear quite distinct from Latin Popula tions, including the Italians. Moreover, the presence of a component of Middle East origin in the island is supported by the distribution of HL-A factors [2,10] and of a Y-linked RFLP [4]. These obser vations support the reports of a substan tial colonization of the southern coastal regions of Sardinia by Punic and Cartha ginian invaders [1].…”
Section: Introductionsupporting
confidence: 74%
“…On the basis of historical, linguistic and classical genetic data, the Sardinians appear quite distinct from Latin Popula tions, including the Italians. Moreover, the presence of a component of Middle East origin in the island is supported by the distribution of HL-A factors [2,10] and of a Y-linked RFLP [4]. These obser vations support the reports of a substan tial colonization of the southern coastal regions of Sardinia by Punic and Cartha ginian invaders [1].…”
Section: Introductionsupporting
confidence: 74%
“…HLA-A29 was associated with NPC among East African Blacks (RR= 19.5;Hall et al, 1982). Among North African NPC, the frequencies of A3, B5 and B15 were increased and AW33, B14 and DR4 decreased (Herait et al, 1983) and yet in another North African population, the Tunisians, no HLA association was found (Betuel et al, 1975 increase in the frequencies of A3 and B5 was observed among German NPC (Kruger et al, 1981), A3 among NPC from Australia (Simons & Shanmugaratnam, 1982) while no associations was reported in other Caucasian populations (Jing et al, 1977;Moore et al, 1983;Beigel et al, 1983). In South East Asia, besides the high NPC incidence Chinese population, there are ethnic groups with mid range incidence of NPC and here we report that results of HLA typing in NPC from one such ethnic group, the Malays.…”
mentioning
confidence: 92%
“…Subsequent association studies among the Chinese have elaborated further HLA association with NPC, notably, an increased risk associated with B58, and a decreased risk for A11 (Chan et al, 1983;Hildesheim et al, 2002;Lu et al, 2003). Among other ethnic groups, however, the pattern of association with HLA alleles is rather different, with A2 appearing protective in Caucasians (Burt et al, 1994), and A11 not conferring protection among north Africans (Betuel et al, 1975;Herait et al, 1983;Dardari et al, 2001). The present study was undertaken to examine further the HLA A and B associations among southern Chinese.…”
mentioning
confidence: 99%